GLUTEN-FREE FLOUR-BASED BREAD CONFICTION - Yuldasheva I. E.; Rakhimova G. G. (Galaxy International Interdisciplinary Research Journal, 2022)
It is hard to imagine our lives today without bread and bakery products. The reason is that almost all people use them every day. Due to the high consumption, various additives are added to wheat flour to ensure its quality. This article gives you a brief overview on corn flour.